DISEMINASI KESELAMATAN JIWA KAPAL NELAYAN PESISIR KABUPATEN KARAWANG JAWA BARAT - Saputra, Rahmad Surya Hadi; Perangin-Angin, Robet; Haris, Dendi; Sutono, Dian; Prasetyono, Untung; Istrianto, Kadi; Surharyanto; Sari, Ratih Purnama; Akbar, Raden Mohamad Adha (Jurnal Abdi Insani, 2024)
The escalating need for animal protein has stimulated the growth of the capture fisheries industry. However, undue carelessness concerning the maintenance and operation of fishing vessels often results in scenarios that pose serious risks, even leading to fatal accidents. In Karawang District, the high spirit of fishermen in setting sail plays a major role in boosting the productivity in the capture fisheries sector. Yet, the awareness of the importance of using personal safety equipment while at sea remains disappointingly low. The Fish Capture Study Program of the Politeknik Kelautan dan Perikanan Karawang set out to organize a training sessions aimed for enhancing the fishermen’s awareness of safety during their voyages. These sessions are a manifestation of the social responsibility in empowering the community and promoting sustainable development. Through presentations, and direct demonstrations, fishermen are instructed on various aspects of safety during their voyage. The training includes techniques for self-preservation at sea, use of the red hand flare, activation of parachute signals, and smoke signals during emergencies, as well as the use of life buoys and life jackets to enhance safety at sea. This community service activity was attended by 20 fishermen residing on the coast of Karawang District. The initiative attempts to strike a balance between the urgency to meet the growing demands for animal protein, and the obligation to promote safe and sustainable practices in the capture fisheries sector.